Enhanced photovoltage in DSSCs: synergistic combination of a silver modified TiO2 photoanode and a low cost counter electrode. Issue 40 (5th April 2016) - Sardar, Samim; Ghosh, Srabanti; Remita, Hynd; Kar, Prasenjit; Liu, Bo; Bhattacharya, Chinmoy; Lemmens, Peter; Pal, Samir Kumar
Abstract : Enhanced photovoltage in the presence of silver modified TiO2 nanocomposites as a photoanode in dye-sensitized solar cells. Abstract : In this study, we have tailored both the active electrode with silver modified TiO2 (Ag–TiO2 ) as well as the counter electrode (CE) with Pt–reduced graphene oxide (Pt@RGO) nanocomposites to realize efficient and low cost devices. The synergistic combination of both modified electrodes leads to an improved light to electrical energy conversion with an overall efficiency of 8%. An increase in the photovoltage ( V OC ) of ∼16% (0.74 to 0.86 V) is achieved using Ag–TiO2 in comparison to the bare TiO2 . This can be attributed to the shifting of the quasi-Fermi level of the TiO2 photoanode close to the conduction band in the presence of Ag nanoparticles (NPs) due to the formation of the Schottky barrier. On the other hand, the facile synthesis of Pt NPs on RGO nanosheets by a photo-reduction method without using chemical reducing or stabilizing agents demonstrates a higher efficiency than Pt as a CE due to the cooperation of the catalytic activity of Pt and the high electron conductivity of the RGO as a stable supporting material having more interfacial active sites. The quantity of Pt in the Pt@RGO nanocomposites is 10 times lower than in the Pt CE which reduces the cost and makes it viable for large scale commercial utilization.